Crystal structure of 4-phenyl-2,4-dihydro-3H-1,2,4-triazole-3-thione, C8H7N3S - Yeo, Chien Ing *; Tiekink, Edward R. T. * (de Gruyter, 2019)
C8H7N3S, monoclinic, P21/c (no. 14), a = 6.0155(1) Å, b = 14.1062(1) Å, c = 10.1990(1) Å, β = 98.871(1)°, V = 855.092(18) Å3, Z = 4, Rgt(F) = 0.0241, wRref(F2) = 0.0609,T = 100(2) K. CCDC no.: 1902322 The molecular structure is shown in the figure. Table 1 contains crystallographic data and Table 2 contains the list of the atoms including atomic coordinates and displacement parameters.